Monitoring částečných výbojů a jejich minimalizace v rozváděči UG ZS1 - Bajánek, Tomáš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2011)
Bakalárska práca sa zaoberá čiastkovými výbojmi v rozvádzači ABB UniGear ZS1. Práca sa zaoberá teoretickým rozborom vzniku čiastkových výbojov, popisom parametrov a možnosťami merania čiastkových výbojov. Zaoberá sa popisom rozvádzača ako elektrického zariadenia a rozborom miest, kde v ňom môže dôjsť k vzniku čiastkových výbojov. Obsahuje popis laboratória na meranie čiastkových výbojov vo firme ABB, popis meracieho zariadenia LDS-6 základný návrh optimalizácie čiastkových výbojov v rozvádzači ABB UniGear ZS1.

Bachelor's thesis deals with partial discharges which occur in switchgear ABB UniGear ZS1. The work deals with the theoretical analysis of partial discharge, a description of the parameters and possibilities of measuring partial discharges. It deals with the description of switchgear as an electrical equipment and analysis of the places where it may lead to formation of partial discharges. The work contains a description of the laboratory for measurement of partial discharges in the company ABB, description of measuring equipment LDS-6 and basic project of optimization of partial discharges in switchgear ABB UniGear ZS1.
Monitoring of partial discharges and their minimization in switchgear UG ZS1
Keywords: Čiastkové výboje; rozvádzač; dutinky; detekcia; Partial discharges; switchgear; cavities; detection